2014
DOI: 10.1093/logcom/exu070
|View full text |Cite
|
Sign up to set email alerts
|

The collapse of the bounded width hierarchy

Abstract: We show that every constraint satisfaction problem over a fixed constraint language that has bounded relational width has also relational width (2, 3). Together with known results this gives a trichotomy for width: a constraint satisfaction problem has either relational width 1, or relational width (2, 3) (and no smaller width), or does not have bounded relational width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(158 citation statements)
references
References 21 publications
4
147
0
Order By: Relevance
“…× D n . For any tuple t ∈ R and any 1 ≤ i ≤ n, we denote by t[i] the value in the i-th coordinate position of t and write t as t [1], . .…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…× D n . For any tuple t ∈ R and any 1 ≤ i ≤ n, we denote by t[i] the value in the i-th coordinate position of t and write t as t [1], . .…”
Section: Preliminariesmentioning
confidence: 99%
“…[27,29,32,6,10]). Recently, it was shown that PC can be used to decide the satisfiability of a problem if and only if the problem does not have the ability to count [2,1]; however, it remains unclear whether backtrack-free search can be used to extract a solution for such a problem after enforcing PC.…”
Section: Introductionmentioning
confidence: 99%
“…Any language preserved by WNU polymorphisms of all arities greater than or equal to 3 has bounded width [9]; this class is extremely large and encompasses all tractable classes discussed above. Finally, it has been shown that every language with bounded width has width (2, 3) [8,24], which allows for fairly efficient solving.…”
Section: Language Classes Solved By Local Consistencymentioning
confidence: 99%
“…In the case of rigid cores, the class of languages with WNU polymorphisms of all arities greater than or equal to 3 can be recognized in polynomial time [8] by combining an alternative characterization involving only two WNU polymorphisms of fixed arity [124] and a variant of the recognition algorithm used for near-unanimity polymorphisms. However, deciding whether an arbitrary language has bounded width is NP-hard [34].…”
Section: Recognition Of Different Families Of Polymorphismsmentioning
confidence: 99%
“…(1) The relational product of two binary relations R and S on a set A is the relation R • S defined to be{(a, b) ∈ A 2 : (a, c) ∈ R and (c, b) ∈ S for some c ∈ A}.…”
mentioning
confidence: 99%